IMPLEMENTASI KEBIJAKAN TATA KELOLA PENYELENGGARAAN PEMILU SERENTAK TAHUN 2019 - Zulkarnaini, Zulkarnaini; Akmal, M; Muklir, Muklir (Jurnal Transparansi Publik (JTP), 2022)
This study looks at how Panwaslih, North Aceh Regency, implemented its governance plans for hosting concurrent elections in 2019. The goal of this study is to examine the governance policy's implementation for the 2019 simultaneous elections, the role of the election supervisory body/Panwaslih in overseeing the elections in the North Aceh district in 2019, as well as the enabling and obstructive factors in the implementation of supervision. The research is descriptive qualitative, the methods for gathering data are observation, interviews, and documentation, and the methods for analyzing the data are data reduction, verification, and conclusion-making. The study's findings demonstrate that the Panwaslih in the Governance of the 2019 Simultaneous Elections has carried out the supervisory role with professionalism. All phases of the 2019 election will be supervised in compliance with Election Law Number 7 of 2017, which was passed in 2017. It is established that the Aceh Regency Panwaslih commits every election violation without showing any preference. All allegations of electoral fraud are investigated by Bawaslu in accordance with Bawaslu rules. Additionally, at the Panwaslih Accountability for the Execution of the 2019 Simultaneous Elections level It is demonstrable that the North Aceh Regency's 2019 General Elections were implemented without incident. Despite the fact that there were still infractions in the field, the Election Supervisors were able to effectively rectify them through preventative measures integrating community participation in supervision.